First aid knowledge among health assigned teachers of primary schools - Pandey, Rakhi; Chauhan, Richa; Dobhal, Sushant; Dabral, Swasti; Nathani, Swati; Negi, Sweety; Rana, Umesh; Negi, Vaishali; Maindola, Varsha; Rawat, Vishal; Sorte, Dipti Y.; Bharadwaj, Rashmi (International Journal of Research in Medical Sciences, 2017)
Background: Every parents of a child knows that it is hard enough to keep their child safe at home but when child goes off to school there is a whole new set up of challenges. Parents totally entrust their children to the schools. They rely on the teachers as their second parents in the institute for learning. They know for a fact that their educators will want no harm to come their way. While they are busy working, they fully believe that their children are well cared for. On the other hand, the teachers have the responsibility to keep an eye on their students. They should make sure that they are comfortable and secured within the four walls of their school. This then calls for their ability to handle even the most stressful situations. So much more, the school staff, especially the health teacher has to be equipped with the knowledge of first aid. Methods: Non-experimental survey study was conducted to assess the knowledge of first-aid among Health assigned teacher working in selected schools of Dehradun city. Using purposive sampling technique 40 samples of different schools of Dehradun city was adopted to select the area. Results: Result shows that the majority of health assign teachers were having average knowledge about first aid i.e. 29 (72.5%) and 10 (25%) were having good knowledge and 1 (2.5%) was having poor knowledge regarding first aid. Majority of participant were female 21 (52.5%). The educational status of most participants was post graduate (67.5%). Majority of the schools were private 25 (62.5%). There is no significant association between socio-demographic variables i.e. Gender, level of schools, year of experience as a health assigned teacher and education provided by teacher, but qualifications of teachers and type of schools was found to have a significant association.(p> 0.05). Conclusions: First aid is the assistance given to any person suffering a sudden illness or injury, with care it is provided to preserve life and to prevent the condition from worsening, and for promoting recovery. It is important that health assigned teachers are equipped with strong, professional competencies. In order for health promotion actions to be sustainable in schools, teachers must be capable, competent and skilled health educators. As they are at prime position to contribute to a nations health gain through the provision of health education for future adults. Based on findings we can say that the health assigned teachers are having average knowledge regarding first aid. Therefore, the health assigned teachers must be equipped with appropriate and upgraded knowledge.